Student’s Perception of TOEFL during Online Learning in Pandemic Outbreak - Jimmi Jimmi; Juniato Sidauruk; Sufi Alawiyah (Scope : Journal of English Language Teaching, 2023)
This research aims to investigate the students’ perceptions towards Test of English as a Foreign Language (TOEFL) during online learning of the pandemic outbreak in Universitas Bina Sarana Informatika. This research used qualitative descriptive method. The researchers gave several questions in the form of questionnaire through google form. Seventy students from different major and status (graduated and not graduated yet) in Universitas Bina Sarana Informatika were chosen as participants. The data were gathered through questionnaires. There were ten questionnaires regarding to students’ perception of the given policy to the participants; and three questionnaires regarding to improve TOEFL competence skill. The result shows that 70,4% of participants prefer to choose Computer Based Test, and 45,1% of participants study TOEFL mainly to have Scholarship. Related to the most difficult part of TOEFL test, there are 36,6% of participants percept Listening Comprehension. Furthermore, in improving TOEFL competence, 43,7% of participants mostly like to watching movie. It indicates that most of the participants considered TOEFL as an essential thing to scale their English proficiency test and as the difficult test in English Proficiency. Furthermore, from the findings, it can also be seen that the challenges and gains encountered by the students are varied.